Effective Governance of Global Financial Markets: an Evolutionary Plan for Reform. (11th July 2013) - Avgouleas, Emilios
Abstract: Two questions remain widely open when it comes to global financial markets. First, what is the raison d'être of open global markets? Second, is it possible to foster open markets without an international governance structure supervising them? Post‐crisis regulatory reform presents an acute paradox. While the content of international financial regulation is changing rapidly, the reform of governance structures is painfully slow. There is no formal governance structure dealing with cross‐border supervision of global financial institutions. In addition, there is no crystallized institutional capacity at the international level dealing with cross‐border crises and the resolution of global institutions. Other areas of concern are the global supervision of systemic risk and the absence of a reliable finance research watchdog dealing with the production of regulatory standards. This article outlines an international governance framework to deal effectively with these concerns. The adoption of the proposed plan would lead to breaking down the territorial link in the supervision of large financial institutions and of systemic risk, without causing intolerable loss of sovereignty. In addition, the proposed structure is premised on a set of explicit values. These would provide a strong signal to global markets that they need to shift their focus from speculation to development goals. Abstract : Two questions remain widely open when it comes to global financial markets. First, what is the raison d'etre of open global markets? Second, is it possible to foster open markets without an international governance structure supervising them?